2017
DOI: 10.1002/clc.22771
|View full text |Cite
|
Sign up to set email alerts
|

Association between modifiable lifestyle and the prevalence of atrial fibrillation in a Chinese population: Based on the cardiovascular health score

Abstract: Ideal health behavior and factors are associated with lower prevalence of AF in a community-based population. Improving healthy behavior and these factors may be beneficial to decrease the prevalence of AF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Higher numbers of ideal CVH factors have been associated with a reduced risk of coronary artery calcification and pulse wave velocity, some well‐established risk predictors in the development of CVD. Furthermore, the vigorous role of ideal CVH protecting against the incidence of acute myocardial infarction, heart failure, atrial fibrillation, and hypertension has been recognized. This convincing evidence indicated that ideal CVH, as described in the AHA 2020 Impact Goal, protects populations from mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Higher numbers of ideal CVH factors have been associated with a reduced risk of coronary artery calcification and pulse wave velocity, some well‐established risk predictors in the development of CVD. Furthermore, the vigorous role of ideal CVH protecting against the incidence of acute myocardial infarction, heart failure, atrial fibrillation, and hypertension has been recognized. This convincing evidence indicated that ideal CVH, as described in the AHA 2020 Impact Goal, protects populations from mortality.…”
Section: Discussionmentioning
confidence: 99%
“…The AHA position statement recommends that individuals and populations meet specific criteria for 7 health metrics, collectively known as the AHA Life's Simple 7 (LS7), to be classified as having ideal CVH . Researchers have established an association between ideal CVH and a decrease in the risk for CVD, non‐CVD, and all‐cause mortality, in addition to lower healthcare costs, improvement in cognitive functioning, and higher quality of life…”
Section: Introductionmentioning
confidence: 99%
“…2 The AHA position statement recommends that individuals and populations meet specific criteria for 7 health metrics, collectively known as the AHA Life's Simple 7 (LS7), to be classified as having ideal CVH. 1 Researchers have established an association between ideal CVH and a decrease in the risk for CVD, [3][4][5] non-CVD, 6 and all-cause mortality, 7 in addition to lower healthcare costs, 8 improvement in cognitive functioning, 9 and higher quality of life. 10 Epidemiological studies identify self-rated health (SRH) as a simple, subjective measure of health status that consistently predicts morbidity and mortality in different populations even after adjusting for sociodemographic characteristics and risk factors for chronic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 27 studies 12,27,29,30,35,36,42,63,69,84,85,91,105,113,[143][144][145][146][147][148][149][150][151][152][153][154][155] were included in our study and Table 3.3 listed the results of associations between number of ideal metrics and CVD related outcomes. In all studies, persons with higher numbers of ideal CVH metrics had a lower risk of overall CVD mortality, 27,30,35,84,113,143,144,146 incidence, 12,29,69,113,143,150 and prevalence 151 than did those with fewer ideal CVH metrics.…”
Section: Study Characteristicsmentioning
confidence: 99%
“…A few studies also indicated that the greatest number of the ideal CVH metrics could eliminate 84% of myocardial infarction incidence, 143 64% of intracranial artery stenosis (ICAS) prevalence, 145 83%-85% of HF incidence, 91, 147 50% of AF incidence, 154 and 56% of AF prevalence 153 compared to those with fewest number of the ideal CVH metrics.…”
Section: Number Of Ideal Cvh Metrics and Cvd Riskmentioning
confidence: 99%